Synthesis, Characterization of Nickel Cobaltite Nanoparticles and Its Use in Removal Methyl Green Dye from Aqueous Solution - Merza , Sundus Hadi; Abduljabar, Maryam Abdulsatar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this study, nickel cobaltite (NC) nanoparticles were created using the sol-gel process and used as an adsorbent to adsorb methyl green dye (MG) from aqueous solutions. The adequate preparation of nickel cobaltite nanoparticles was verified using FT-IR, SEM, and X-ray diffraction (XRD) studies. The crystalline particle size of NC nanoparticles was 10.53 nm. The effects of a number of experimental variables, such as temperature, adsorbent dosage, and contact time, were examined. The optimal contact time and adsorbent dosage were 120 minutes and 4.5 mg/L, respectively. Four kinetic models—an intraparticle diffusion, a pseudo-first-order equation, a pseudo-second-order equation, and the Boyd equation—were employed to monitor the adsorption process. Modeling of the experimental data showed that the pseudo-second-order model accurately captured the adsorption kinetics due to the high value of the correlation coefficients (R2). MG dye is gradually adsorbed to the NC nanoparticles through boundary layer diffusion and intraparticle diffusion. The results of the thermodynamic analysis showed that the MG dye adsorption was endothermic and a nonspontaneous phyisorption process.